2019
DOI: 10.1253/circj.cj-18-0999
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Time Interval Between Mitral and Tricuspid Valve Opening in Patients With Heart Failure

Abstract: Background:We used dual Doppler echocardiography to measure the time interval between the mitral and tricuspid valve opening (MO-TO time), which we expected would reflect the balance between left and right ventricular hemodynamics. Methods and Results:We prospectively enrolled 60 patients with heart failure (HF) and sinus rhythm. The MO-TO time was measured in addition to routine echocardiography parameters, invasive hemodynamic parameters and plasma B-type natriuretic peptide (BNP) level in all patients. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
(14 reference statements)
1
18
0
Order By: Relevance
“…In the present case, echocardiographic findings of a transmitral restrictive filling pattern along with a time lag in transtricuspid inflow suggested markedly elevated LA pressure . In addition, pressure recordings revealed that the early cross‐over of the PAW and LV pressures resulted from markedly elevated V‐waves of PAW pressure and early‐diastolic reversal of the RA‐RV pressure gradient.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In the present case, echocardiographic findings of a transmitral restrictive filling pattern along with a time lag in transtricuspid inflow suggested markedly elevated LA pressure . In addition, pressure recordings revealed that the early cross‐over of the PAW and LV pressures resulted from markedly elevated V‐waves of PAW pressure and early‐diastolic reversal of the RA‐RV pressure gradient.…”
Section: Discussionsupporting
confidence: 48%
“…The finding was confirmed by color M‐mode Doppler as well as continuous‐wave Doppler (Figure and Movie ). Transmitral Doppler flow showed a restrictive filling pattern, whereas transtricuspid Doppler flow showed monophasic filling at end‐diastole (Figure ), and thus, transmitral filling obviously preceded transtricuspid filling (Figure and Movie ), indicating elevated LA pressure . Precise observation of atrioventricular (AV) valves and the inter‐ventricular septum during early diastole revealed a unique time sequence: The mitral valve opened soon after the systolic phase, and the inter‐ventricular septum immediately shifted toward the RV and subsequent TR occurred in the early‐diastolic phase (Figure and Movie ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Theoretically, this score increases in accordance with the elevation of PAWP because the pressure crossover between the left atrium and the decay of the left ventricle happens earlier with the increase in the LA peak v pressure, which causes PAWP elevation, 14,15 and also the relative timing of atrioventricular valve opening depends on the relationship between RA and LA pressures. 9 Figure 1 VMT scoring. Apical four-chamber views in early diastole and corresponding subcostal views (top), schematic presentation of pressure waveforms on the basis of direct recording of PAWP (middle) and RAP (bottom) are presented.…”
Section: Vmt Scoringmentioning
confidence: 99%
“…4,8 Early opening of the mitral valve (MV) relative to the tricuspid valve (TV) in elevated LVFP has recently been recognized, and the echocardiographic time delay of right ventricular (RV) inflow relative to left ventricular (LV) inflow assessed using a dual-Doppler system was reported as a parameter of LVFP. 9 Although the concept is quite unique and reasonable considering the pathophysiologic consequence of elevated LVFP, the index has two specific limitations: lack of consideration of central venous pressure and the need for special equipment. We assumed that the visually assessed time delay of TV relative to MV opening could be a feasible and alternative marker of LVFP.…”
mentioning
confidence: 99%
“…In this issue of the Journal, Sugahara et al proposed a novel echocardiographic parameter using the dual Doppler system with a focus on the interaction between the right ventricular (RV) and LV functions. 13 In addition to LV systolic and diastolic function, assessment with a combination of RV function is challenging.…”
mentioning
confidence: 99%